PowerPoint 4 for Windows for dummies - Lowe, Doug (San Mateo, California : IDG Books, 1994)
Learn how to create PowerPoint presentations for Windows the easy way. The book covers version 4.
Part I: basic PowerPoint stuff -- Part II: Dressing up your presentations -- Part III: Pictures, charts, and grunts -- Part IV: Working with files -- Part V: The part of tens
Includes index.
Keywords: MICROSOFT POWERPINT (COMPUTER FILE)